Blockchain-Based Software Architecture Development for Service Requirements With Smart Contracts. - Zhu, Yan; Guo, Qian; Yin, Hongjian; Liang, Kaitai; Yau, Stephen S. (Computer (00189162), 2021)
We review the background, classification, specifications, and related aspects of using smart contracts in blockchain services and introduce a framework for generating a general software architecture in the context of contract-oriented programming.